Kinetics of the Oxidation of Ethyl Acetate by Potassium Dichromate. - JOSHI, D.R.; GUARD, H.Z.; JOSHI, H.M.; NAGAR., T.N. (Asian Journal of Chemistry, 2010)
Potassium dichromate exists as an important oxidising agent. In this paper, we report the kinetics of oxidation of ethyl acetate by potassium dichromate in acid-water and solvent-water mixtures at different temperatures. Also we have reported the dependence of rates of reaction on concentration of oxidant and substrate.